Vozes que não podem ser silenciadas: propostas didáticas sobre práticas e estratégias de leitura com autores afro-brasileiros - Ventura, Tuanny Bastos (2024)
This dissertation seeks to explore the importance of reading in our lives and how present it is in all areas. Even before we learn to read and write. Therefore, it is essential that the teaching of reading is also based on social practices - reading in its social uses. Because, even if students are in more advanced grades such as high school, it is still possible to notice resistance and great difficulty in reading. In this sense, this work's main objective is to propose reading activities of Afro-Brazilian literature through the Reading Circle and Reading Strategies that aim to encourage and consolidate reading practices for students in the 1st and 2nd years of high school. We have established specific objectives: (1) to encourage the reading of Afro-Brazilian authors; (2) identify and analyze reading strategies and their importance in reading practices (3) encourage the teaching of shared reading; (4) develop reading activities based on reading strategies and the Reading Circle; To conduct this work, we used the theoretical contributions of Afro-Brazilian literature with Duarte (2008), Conceição Evaristo (2014, 2018), Chimamanda Ngozi Adichie (2019) and Jenyffer Nascimento (2014), the studies of Paulo Freire (1989; 2003 ) Martins (1998), Eliane Yunes (1999), Souza (2012), Vincent Jouve (2002) on the different definitions that reading can have; We sought support in the Literacy studies of Kleiman (2004) and Soares (2009), Isabel Solé (1998) and Girotto and Souza (2010) on reading strategies and Rildo Cosson (2009; 2014) to approach the Reading Circle. The methodological procedure consists of a qualitative and descriptive nature. We will present two didactic proposals: the first on reading strategies with the methodology of before - during and after reading and the second, and the second, on the Reading Circle relating how we can use reading strategies. Both activities include reading Afro-Brazilian literature aimed at encouraging and consolidating reading practices for students in the 1st and 2nd years of high school. Six main works will be used in the activity: the poem Vozes Mulheres, by Conceição Evaristo; the song Mama África, by Chico César; the Mãe Negra monument, by Júlio Guerra; the short story “Maria”, by Conceição Evaristo; the comic strip Santos 06, by Leandro Assis; the poem Identity, by Jennifer Nascimento. We hope that the suggested activities can contribute to encouraging Afro-Brazilian reading and greater reading proficiency among students. Furthermore, we hope that the research developed will also be a contribution to academia and future teachers in the field of education.